2020
DOI: 10.1111/iju.14322
|View full text |Cite
|
Sign up to set email alerts
|

Is the membranous urethral length related to postoperative urinary incontinence after holmium laser enucleation of the prostate?

Abstract: Abbreviations & Acronyms BPH = benign prostatic hyperplasia CI = confidence interval HoLEP = holmium laser enucleation of the prostate IPSS = International Prostate Symptom Score MRI = magnetic resonance imaging mRUL = minimal residual membranous urethral length MUL = membranous urethral length OR = odds ratio PSC = periurethral sphincter complex PV = prostate volume PVR = post-void residual urine volume Q ave = average flow rate by uroflowmetry Q max = maximum flow rate by uroflowmetry QOL = quality of life R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the widest randomized controlled trial to date, Thomas et al have [8] reported a 7% rate of incontinence in the first 6 months after Greenlight photovaporisation of the prostate. Regarding holmium laser enucleation of the prostate (HoLEP0, the most widely used EEP technique actually used, several predictive factors have been reported [9 ▪ ,10]: membranous urethral length on preoperative magnetic resonance imaging, patient age, elevated body mass index, operative time/prostate size, experience of the surgeon. To date, most of cases of transient incontinence lead to conservative management, including physiotherapy.…”
Section: Epidemiologymentioning
confidence: 99%
“…In the widest randomized controlled trial to date, Thomas et al have [8] reported a 7% rate of incontinence in the first 6 months after Greenlight photovaporisation of the prostate. Regarding holmium laser enucleation of the prostate (HoLEP0, the most widely used EEP technique actually used, several predictive factors have been reported [9 ▪ ,10]: membranous urethral length on preoperative magnetic resonance imaging, patient age, elevated body mass index, operative time/prostate size, experience of the surgeon. To date, most of cases of transient incontinence lead to conservative management, including physiotherapy.…”
Section: Epidemiologymentioning
confidence: 99%
“…TUI is one of the most disturbing side effects of this surgical technique because a substantial portion of patients recover on their own in 90 days on average, but occasionally it reduces the subject's quality of life. Despite the fact that HoLEP has some benefits, surgeons may strive to avoid it for the aforementioned reasons [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TUL should be evaluated within 3 months after surgery. Studies have reported that many variables such as surgeon experience, diabetes mellitus, body mass index (BMI), prostate volume, operation time, and membranous urethra length are risk factors for TUL 6,7 . However, during the surgery, the external urethral sphincter (EUS) can be damaged by manipulation of the resectoscope sheath, which may lead to TUL.…”
Section: Introductionmentioning
confidence: 99%